Programa “Vida na Comunidade” para familiares de jovens com deficiência intelectual - Zutião, Patricia (2016)
This research aimed to evaluate the effectiveness of the "Community Life Program" for parents/family in order to promote independence in life activities in the community for young people with Intellectual Disabilities. Participants were four young people with intellectual disabilities aged 19-29 years who formed dyads with their family member. The research took place in two cities in São Paulo State, Brazil, in community places near the residence of these young people. With dyads 1 and 3 it was worked shopping activities and with the dyads 2 and 4 it was worked activities related to moving around community. It was employed the intermittent multiple baseline design across subjects to verify the effects of program implementation and to demonstrate the validity of experimental control and manipulation of the study variables. The independent variable was introduced at different moments for participants. The dependent variable was analyzed before, during and after the implementation of the program. The “Community Life Program” was employed based in theoretical and practical intervention sessions. In the theoretical sessions it was used instructional material to assist parents/family members during the sessions and also in the absence of the researcher. The practice sessions were recorded and analyzed by the observation protocol. The results showed that, when the intervention was started with the implementation of the program, parents/family started demonstrating more appropriate responses, which favored the learning of young people with intellectual disabilities, which increased the percentage of independence in performing the activities. These results were maintained over time in all dyads and generalized to other contexts in dyads 1, 2 and 4. The dyad 3 did not perform generalization sessions due to non-availability of the mother. The good performance achieved by the participants may have been possible due to changing environmental contingencies provided from the implementation of the "Community Life in the program." It is noteworthy that teaching the activity for each of the young people provided learning in various skills that generalized to other functional activities. This study presents contributions on the implementation of a program to assist parents / family in education of young people with intellectual disabilities, especially with regard to the teaching of adaptive activities in the "Community Life" to promote the inclusion and participation in society and improve quality of life.